Volleyball Modifications To Improve Students' Basic Movements In The Learning Outcomes Of The Volleyball Game Muhammadiyah 1 High School, Malang City - Azizi, Arbahan; Kusmawati, Wiwik; Kurniasari, Praharisti; Pradipta, Anangga Widya (Jurnal Ilmiah Mandala Education (JIME), 2024)
The aim of this research is to improve the learning outcomes of basic volleyball movements with volleyball modifications for students at SMA Muhammadiyah 1 Malang City. This research is Classroom Action Research (CAR), which consists of two cycles. The subjects in this research were 21 students in class XI SMA Muhammadiyah 1 Malang City. Data collection techniques use tests and observations. Data analysis uses qualitative descriptive techniques based on percentage qualitative analysis. The research results in the pre-cycle were only 4 students who passed (19.05%) and 17 students did not pass (80.95%). In the first cycle, the learning outcomes of 11 students who had passed (52.38%) were obtained and 10 students had not yet passed (47.61%). With average gains in affective (81.33%), psychomotor (74.95%) and cognitive (68.33%). In cycle II, the learning outcomes of 18 students who had passed (85.71%) were obtained and 3 students had not yet passed (14.29%). With average gains in affective (81.38%), psychomotor (77.33%) and cognitive (81.81%). Based on the research results, it was concluded that volleyball modifications can improve learning outcomes for the basic movements of volleyball in students at Muhammadiyah 1 High School, Malang City.